ASSESSMENT LITERACY MEASURES: A COMPREHENSIVE BIBLIOMETRIC ANALYSIS - Norazida Ibrahim; Muhammad Azhar Zailani; Harris Shah Abd Hamid (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Assessment literacy, a crucial component in education, plays a pivotal role in ensuring effective teaching and learning outcomes. The growing complexity and diversity of assessment practices in education underscore the necessity for educators to possess a nuanced understanding of assessment literacy. Despite its acknowledged importance, a consolidated overview of the research efforts in assessment literacy measures is lacking. This bibliometric review aims to investigate the scholarly landscape surrounding assessment literacy measures systematically. By delving into the literature, this study seeks to uncover research trends, influential contributors, and co-authorship countries’ collaboration within the realm of assessment literacy in education. Scopus, a widely recognized scholarly database, serves as the primary source for this bibliometric review. A systematic search strategy employing relevant keywords and inclusion criteria retrieves a comprehensive dataset. Bibliometric indicators, including citation analysis, co-authorship networks, and keyword co-occurrence, are utilized to analyze and visualize the intellectual structure of assessment literacy measures research. The examination of keyword trends is anticipated to provide valuable insights into emerging areas of interest, illuminating the evolving discourse within the field. This thorough analysis aims to propel the field forward by addressing current challenges and inspiring future innovations in assessment literacy measures within the educational landscape.